Early Effective Antibiotic Therapy and Meningitis following a Bloodstream Infection in Hospitalized Infants: A Cohort Study - Ericson, Jessica E.; Greenberg, Rachel G.; Smith, P. Brian; Clark, Reese H.; Benjamin, Daniel K., Jr.; Kilpatrick, Ryan (American Journal of Perinatology, 2025)
This study aimed to evaluate the role of early effective antibiotic therapy in preventing secondary meningitis as a sequelae of bacterial bloodstream infections (BSI).In this multicenter cohort study, we identified blood cultures that were positive for Group B Streptococcus (GBS), Staphylococcus aureus, Escherichia coli, and other non-E. coli gram-negative bacteria that had a corresponding cerebrospinal fluid sample collected ≤7 days after the positive blood culture among infants discharged from a neonatal intensive care unit managed by the Pediatrix Medical Group 2002 to 2020. The odds of secondary meningitis for early effective antibiotic therapy versus delayed antibiotic therapy were compared using an adjusted logistic regression model. The odds of secondary meningitis following GBS BSI were compared for infections treated with empirical vancomycin versus β-lactam antibiotic.Secondary meningitis was identified in 11% of 5,967 BSI. Early effective antibiotic therapy was not associated with a reduced odds of secondary meningitis for GBS (adjusted odds ratio [aOR]: 1.17; 95% confidence interval [CI]: 0.82–1.66) or E. coli (aOR: 1.06; 95% CI: 0.82–1.38); however, was associated with decreased odds for non-E. coli gram-negative bacteria (aOR: 0.69; 95% CI: 0.49–0.98) and S. aureus (aOR: 0.51; 95% CI: 0.34–0.74). GBS BSIs were more often complicated by meningitis when vancomycin was used empirically compared with β-lactam antibiotic (aOR: 2.01; 95% CI: 1.28–3.14).Early effective antibiotic therapy for BSI in infants did not reduce the odds of secondary meningitis caused by GBS or E. coli; however, early effective antibiotic therapy did reduce episodes due to non-E. coli gram-negative bacteria and S. aureus.
Keywords: neonate; infection; sepsis; meningitis; antibiotics